Randomized reverse marker strategy design for prospective biomarker validation. (18th March 2014) - Eng, Kevin H.
<x xml:space="preserve">Abstract</x> We describe a novel study design for validating marker‐based treatment strategies meant to select among possible therapeutic options using a biologic marker. Studying existing designs in realistic scenarios, we demonstrate that this design is more than four times more efficient for testing the interaction between a marker and its intended treatment. Our analysis employs a simple parametric framework that uncovers systematic biases in currently proposed designs and suggests how they may be accommodated or enumerated. In the context of markers for choosing a treatment for recurrent ovarian cancer, our proposal requires sample sizes on the order of recently completed phases II and III studies making validation studies for this clinical decision scenario viable. © 2014 The Authors. Statistics in Medicine Published by John Wiley & Sons Ltd.